The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1182/blood-2014-03-563817
|View full text |Cite
|
Sign up to set email alerts
|

HLA-haploidentical stem cell transplantation after removal of αβ+ T and B cells in children with nonmalignant disorders

Abstract: Key Points Removal of αβ+ T and CD19+ B cells is an effective strategy for successful HLA-haploidentical hematopoietic stem cell transplantation. The high probability of disease-free survival renders this transplant option attractive for any child with a nonmalignant disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
338
2
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(360 citation statements)
references
References 29 publications
13
338
2
7
Order By: Relevance
“…[56][57][58] In this scenario, Schumm et al 59 recently introduced an innovative approach of graft manipulation, which consist in depleting the leukapheresis product of only TCR αβ + T cells and CD19 + B cells, thus retaining large numbers of crucial immune effectors such as TCR γδ + T cells, NK cells and DCs; this method has been safely tested in a cohort of children by Locatelli and colleagues. 60 Although G-CSF mobilization is known to alter phenotype and cytokine polarization of transplanted immune cells, very few data are available on the impact of plerixafor on allogeneic graft cell subsets, as it is not approved for administration in healthy donors yet. Two recent studies in mice compared the effect of G-CSF and plerixafor on T-cell alloreactivity, showing that alterations in the T-cell phenotype and cytokine gene expression profile characteristic of G-CSF mobilization do not occur with plerixafor.…”
Section: Mobilized Pbsc: the Immunological Perspective F Saraceni Et Almentioning
confidence: 99%
“…[56][57][58] In this scenario, Schumm et al 59 recently introduced an innovative approach of graft manipulation, which consist in depleting the leukapheresis product of only TCR αβ + T cells and CD19 + B cells, thus retaining large numbers of crucial immune effectors such as TCR γδ + T cells, NK cells and DCs; this method has been safely tested in a cohort of children by Locatelli and colleagues. 60 Although G-CSF mobilization is known to alter phenotype and cytokine polarization of transplanted immune cells, very few data are available on the impact of plerixafor on allogeneic graft cell subsets, as it is not approved for administration in healthy donors yet. Two recent studies in mice compared the effect of G-CSF and plerixafor on T-cell alloreactivity, showing that alterations in the T-cell phenotype and cytokine gene expression profile characteristic of G-CSF mobilization do not occur with plerixafor.…”
Section: Mobilized Pbsc: the Immunological Perspective F Saraceni Et Almentioning
confidence: 99%
“…Two recent studies on αβ-depleted HHCT reported CIs of acute ⩾ grade 3GvHD as 0 and 15%, respectively. 5,16 In our present study, the incidences of acute and chronic GvHD were acceptable; notably, no patient died of GvHD.…”
Section: Discussionmentioning
confidence: 74%
“…Recent reports on αβ-depleted HHCT in children with malignant or nonmalignant disease revealed low TRM rates of less than 10%. 5,16 Relapse was the major treatment failure in our present series. In studies of HHCT using αβ-or CD3-depleted grafts for pediatric patients with malignant disease, the major cause of death was relapse, especially in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations